Implementasi Program Deteksi Dini Perkembangan Balita berbasis Teknologi dalam Upaya Skrining Gangguan Perkembangan Anak di Desa Carangsari, Kecamatan Petang, Kabupaten Badung, Bali: Pengabdian - Ni Made Egar Adhiestiani; Komang Yogi Triana; I Made Pradipta (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Children aged 0–6 years are in a golden phase of growth and development because the brain develops optimally in intellectual, emotional, and social aspects. Delayed early detection during this period can increase the risk of disabilities due to late treatment. Posyandu Balita plays a crucial role as a forum for parents to monitor their children's growth and development. However, many Posyandu still face obstacles, such as non-digital data collection systems, less than optimal education, and ineffective task allocation, thus reducing the quality of services. This community service activity aims to improve the quality of Posyandu Balita services through the use of a technology-based Pre-Screening Development Questionnaire (KPSP) at the Posyandu in Carangsari Village for early detection of child developmental disorders. The activity was carried out on September 25, 30, and October 2, 2025, through preparation, implementation, and evaluation stages. The results of the activity showed an increase in the knowledge of health workers, cadres, and Posyandu participants, facilitating task allocation, documenting child data, implementing health education, and reducing the risk of data loss.